Chronic axonal idiopathic polyneuropathy: is it really benign. Issue 5 (October 2020) - Samuelsson, Kristin; Press, Rayomand
Abstract : Purpose of review: Chronic idiopathic axonal polyneuropathy (CIAP), a common neurological condition, is considered to be a benign neurological condition with a small risk of disability. However, many studies have shown a reduced quality of life and a nonnegligible affection of daily activities in patients with CIAP. Here we summarize recent data about CIAP. Recent findings: We discuss some of the latest articles regarding risk factors, comorbidities, and possible pathogenic factors regarding CIAP. Patients with chronic polyneuropathy have impaired walking capacity, disturbed balance, and an increased risk of falls. Idiopathic polyneuropathy has a negative impact on activities of daily living. Patients with CIAP may develop plantar ulcers and neuropathic arthropathy. Small fiber involvement may occur, and two recent studies indicate that neuropathic pain is present in about two thirds of the CIAP group. Furthermore, patients with CIAP with neuropathic pain have increased fatigue and poorer emotional well being. Summary: Despite the relatively mild motor impairment seen in most patients with CIAP, the condition causes limitations in life with decreased mobility, pain, and affection of basal daily activities. Because the pathogenesis of CIAP in unclear, there is no disease modifying treatment. Further studies regarding pathogenesis, and randomized controlled clinical trials regarding possible treatment options are needed.